A Romany of the Snows, vol. 1 : Being a Continuation of the Personal Histories of "Pierre and His People" and the Last Existing Records of Pretty Pierre - Parker, Gilbert, 1862-1932 (Salt Lake City, UT : Project Gutenberg, 2004)
"A Romany of the Snows" by Gilbert Parker is a novel likely written during the late 19th century. This work serves as a continuation of Parker's earlier stories about Pierre and his adventures among the rugged landscapes of the Far North, highlighting themes of love, loyalty, and the human spirit against the backdrop of natural beauty and cultural conflict. At the start of the story, we are introduced to Pierre, a half-breed gambler and adventurer, who enjoys reflecting on his past while resisting the pull of impending adventures. The narrative opens with lively dialogue among Pierre and his friends at a Hudson's Bay Company post, establishing a playful camaraderie. Pierre recounts the tale of a girl dressed as a man who rides hard to meet her lover, setting in motion a thrilling adventure as Pierre decides to assist her in reaching her destination and confronting the dangers that follow. This opening hints at deeper explorations of character and emotional stakes, blending humor with the earnestness of human connection against a backdrop of adventure and peril. (This is an automatically generated summary.)
Across the jumping sandhills -- A lovely bully -- The filibuster -- The gift of the simple king.
Release date is 2004-07-01
This eBook was produced by David Widger
Keywords: Canada, Northern -- Fiction; Short stories, Canadian